DEVELOPMENT OF TOURISM VILLAGES BASED ON LOCAL WISDOM AS AN EFFORT TO INCREASE COMMUNITY INCOME IN LEMBANG RANDANAN - Mercyliani Rerung; Jemi Pabisangan Tahirs; Yohanis Lotong Ta'dung (OIKONOMIA: Journal of Economics and Management Science, 2023)
The research problem is what is the role of the community in efforts to increase people's income in Lembang Randanan. The research objective was to determine the development of a tourism village based on local wisdom as an effort to increase people's income in Lembang Randanan. The type of research used is descriptive qualitative research. The type of data used is primary data, namely data obtained or collected directly in the field through interviews with information related to research problems and other data related to this research problem. The results of the study show that Lembang Randanan can be developed into a tourist village because of its many tourism potentials such as natural tourism, man-made tourism and cultural tourism